Content and Value Integrated Learning: Perspectives, Curriculum and Perceptions in the Private University Contexts of Bangladesh - Begum, Fatema; Kamal, Md Asif (Universitas Teuku Umar, 2024)
In this consumerist world, the necessity of teaching ethics, values, and humanity seems to secure a marginal space in any curriculum emphasizing only on content teaching of the subjects associated to shape the graduates as sellable candidates in the job market. Since the ultimate vision of teaching and learning is expected to reshape or build ideal human beings with moral, ethical, and humane qualities, the teaching of ethics and values should be integrated along with the content teaching of the subjects in undergraduate programs. Hence, the vision of developing professional ethics, community ethics, self-esteem, personality, and character should be reflected in and taught through the curriculum. The purpose of this study is to investigate whether human values and ethics are emphasized in the objectives of the curriculum and course content of the departments of English in Bangladeshi private universities. This paper also aims to identify the gap created by the absence of humanizing study contents in the undergraduate English program curriculums of private universities in Bangladesh and provide suggestions to fill the vacuum. After the content analysis of collected curriculums, a significant gap in the inclusion of humanizing study contents in these undergraduate English curriculums to develop moral and ethical faculties among the learners was traced. The study came up with suggestions for adjustment in the university curriculum to fill this vacuum by integrating content and value learning together adopting a holistic approach to nurture humane and moral behavior.